Additive manufacturing via direct ink writing of customized silicone foam with glycerol as dispersed phase for diverse applications - Tie, Kenrick Weiting; Sim, Jia Huey; Tey, Jing Yuen; Yeo, Wei Hong; Lee, Zhi Hua; Ng, Law Yong; Bee, Soo Tueen; Lee, Tin Sin; Abdullah, Luqman Chuah (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Direct ink writing (DIW) enables the additive manufacturing of silicone elastomers, offering an alternative to traditional moulding and casting methods for applications from healthcare products to machine–human interaction sensors. Polydimethylsiloxane (PDMS) foam, a porous silicone elastomer, is valued for its elasticity, chemical and thermal resistance, hydrophobicity, and biocompatibility. The emulsion templating method is a simple and cost-effective approach to create silicone foams by incorporating and later removing a sacrificial dispersed phase from the PDMS precursor. This study developed glycerol/PDMS emulsion-based inks for DIW using high-shear centrifugal mixing, with ethanol as a solvent to remove the glycerol template, creating silicone foam. An optimal glycerol dosage of 50 parts per hundred rubber (phr) produced foam with 27.63% porosity and pore diameter up to 4.66 µm. Each 10 phr increase in glycerol content raised porosity by 10% and average pore diameter by 2 µm. Both tensile and compressive behaviour inversely correlated with porosity, with a 10% porosity rise in the silicone foam reducing tensile strength by 0.07 MPa and stiffness by 0.02 MPa. Models with strong data alignment were developed to benefit researchers in 3D printing to customize silicone foams (pore properties, mechanical properties, compressive properties) based on specific application requirements.